KNOW-HOW AS AN OBJECT OF INTELLECTUAL PROPERTY RIGHTS MANAGEMENT AS PART OF AN ENTERPRISE'S INTANGIBLE ASSETS - SVYSTUN, TETYANA; KONSTANTYNOVA, TETYANA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Secrets of know-how production in the world's leading companies are a major component of assets. That is, for such companies it is the main active basis that provides income. International companies are focused on employees who are able to increase the overall intellectual level of companies and make changes, improve activities. Ukrainian business first came across the term «know-how» when concluding contracts with foreign suppliers of equipment, supplemented by various technological information about the rules of its operation, generally referred to in the know-how contracts. This term is enshrined in business to denote a set of knowledge and experience in a field of activity that have scientific, technical and commercial value and can have practical application. Such useful information can take different forms - technical, technological, commercial, managerial, financial and others. Know-how is the oldest form of protection of intellectual property. This is a very effective regime for entrepreneurs to protect their rights to any innovation, as, unlike patenting, it is not limited in time and does not disclose the essence of the innovation.The article considers a special object of intellectual property rights «know-how» from the point of view of its management as a component of the intangible assets of an enterprise, namely, its identification; criteria to be met by the results of intellectual activity in the know-how mode; substantiation of the possibility of registration as part of intangible assets in the legislation of Ukraine; the advantages and disadvantages of protecting the results of intellectual activity in the know-how regime in comparison with other regimes, which is important for making management decisions; approaches to assessing the value of this object. The most famous and successful examples of the results protection of intellectual activity in the know-how mode in the world are considered. The legislative acts of Ukraine, which contain the definition of know-how, are presented. A generalized definition of this concept is given.
Keywords: know-how; intellectual property; results of intellectual activity; innovations; intangible assets of the enterprise